THE EFFECT OF CREDIT RISK ON FINANCIAL PERFORMANCE OF CONVENTIONAL PEOPLE'S BANKS IN INDONESIA (Comparative Study between Privately Owned and Local Government Owned BPRs) - Reza Surya Akdiwidjaya; Wisnu Mawardi (RADJA PUBLIKA, 2025)
People's Economic Banks (BPR) have a strategic role in supporting the local economy through financial intermediation, particularly in the Micro, Small, and Medium Enterprises (MSMEs) sector. This study aims to analyze the effect of Non-Performing Loans (NPL), Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), and Firm Size on Return on Assets (ROA) in Private BPRs and Regional Government BPRs in Indonesia. The research method used is quantitative with a multiple regression approach, using secondary data from the annual financial reports of Private BPRs and Regional Government BPRs for the 2019-2024 period. Sample selection was carried out using a stratified random sampling method based on data published by the Financial Services Authority (OJK). From the total population, 92 Private BPRs and 92 Regional BPRs were obtained with a total of 1100 initial observations. Then outlier trimming was performed to increase validity, resulting in 302 observations of Private BPRs and 488 observations of Regional BPRs for analysis. Data processing was carried out using SPSS software version 26.0 The results of the study indicate that in Private BPRs, the NPL variable has a significant negative effect on ROA, CAR has a significant positive effect on ROA, LDR has a significant positive effect on ROA, while Firm Size has no significant effect on ROA. In Regional BPRs, the results show that NPL has a significant negative effect on ROA, CAR has a significant positive effect on ROA, LDR has no significant effect on ROA, while Firm Size has a significant positive effect on ROA. The coefficient of determination (Adjusted R²) is 0.209 or 20.4% for Private BPRs and for Regional BPRs it is 0.204 or 20.4%, the independent variables are able to explain variations in ROA. The implications of this study emphasize the importance of controlling non-performing loans (NPLs), strengthening capital (CAR), and effectively channeling quality credit (LDR) in improving the financial performance of rural banks (BPR). Furthermore, asset scale management (firm size) needs to be optimized, particularly in regional BPRs, to contribute more significantly to increased profitability. This study provides theoretical contributions to the banking literature on factors influencing BPR profitability and provides practical input for bank management and regulators in formulating regional banking policies.